Payment Issues in Industrialized Building System (IBS) Projects in Malaysia: Towards a Better Approach - Mohd Nasrun Mohd Nawi; Salman Riazi Mehdi Riazi; Radzi Ismail; Muhammad Fazlisha Shaharizan; Riduan Yunus; Omar Saleh Alhawatmeh (International Journal of Supply Chain Management, 2019)
Industrialised Building System (IBS) was first implemented in Malaysia during the year 1960s and since then it has shed light on the many advantages this system has to offer such as having a systematic and efficient deliverable of fabricated factory-made products, reduced construction period, improved safety on site and many more. Nevertheless, despite the benefits, the level of uptake till today is still way lower than expectation and one of the main contributors to this dilemma is the payment issues that surround projects that uses IBS system. Due to the different nature of work between IBS and conventional in-situ construction, there is a need for proper handling of payment mechanisms so as to not cause burden to any party which would contribute to poor IBS adoption rate. This paper therefore explores the risks associated with IBS uptake, the payment issues surrounding its projects in Malaysia, the way forward and to propose other payment method that suits Malaysia. Besides performing extensive literature reviews, expert opinion was also obtained by interviewing four (4) Malaysian construction industry practitioners from different supply chains of an IBS project with each of them possessing a minimum of 25 years of working experience. Their vast experience was important in getting an insight on the real-world scenario of the subject matter. In the end, it was found that IBS adoption in Malaysia is generally still at far from convincing and poor payment mechanism was a major contributor to this scenario thus, to improve the situation, initiatives should come not only from the government bodies but also from financial institutions; and attention should be placed from both technical and procurement aspects if any improvement on IBS uptake are to be expected.